2005
DOI: 10.1021/es048232b
|View full text |Cite
|
Sign up to set email alerts
|

Bioreduction of Uranium:  Environmental Implications of a Pentavalent Intermediate

Abstract: The release of uranium and other transuranics into the environment, and their subsequent mobility, are subjects of intense public concern. Uranium dominates the inventory of most medium- and low-level radioactive waste sites and under oxic conditions is highly mobile as U(VI), the soluble uranyl dioxocation (UO2)2+. Specialist anaerobic bacteria are, however, able to reduce U(VI)to insoluble U(IV), offering a strategy for the bioremediation of uranium-contaminated groundwater and a potential mechanism for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
197
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(226 citation statements)
references
References 23 publications
20
197
3
Order By: Relevance
“…[64,65] With this study, the potential of bulk reactions with selected additives for providing mechanistic information on aqueous contaminant removal has been demonstrated. This applicable technique can be very useful to obtain qualitative information on Fe 0 removal mechanisms for several contaminants; particularly for other radionuclides, metals and some organics which are known to interact with iron oxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[64,65] With this study, the potential of bulk reactions with selected additives for providing mechanistic information on aqueous contaminant removal has been demonstrated. This applicable technique can be very useful to obtain qualitative information on Fe 0 removal mechanisms for several contaminants; particularly for other radionuclides, metals and some organics which are known to interact with iron oxide.…”
Section: Discussionmentioning
confidence: 99%
“…At Bodo Canyon Site (Durango, Colorado) uranium was present nearly exclusively as U(VI). [64,65] Another important fact in favor of U(VI) co-precipitation with aging corrosion products is given by Morrison et al [22] , who conducted laboratory column experiments under anoxic conditions and could not accurately model their results according to reductive precipitation or U(VI) adsorption onto Fe(III) oxides. They stated that "while a reductive precipitation mechanism is not inconsistent with the results of the laboratory column experiment, the decrease in Eh in the bulk is suspect.…”
Section: Arguments For U(vi) Co-precipitation With Aging Corrosion Prmentioning
confidence: 99%
“…Subsequent studies have also reported biogenic uraninite particle sizes in the 2 to 10 nm range and slight but significant contraction of the first U-U shell (Renshaw et al 2005;Singer et al 2006;Senko et al 2007;Burgos et al 2008;Komlos et al 2008). Similar results have been reported for uraninite nanoparticles produced by abiotic reduction of U(VI) by green rust (O'Loughlin et al 2003).…”
Section: Structure and Composition Of Biogenic Uraninitementioning
confidence: 91%
“…U(V) is unstable as an aqueous complex (Nagaishi et al 1996), and it is therefore possible that enzymatic reduction proceeds from U(VI) to U(V), followed by disproportionation to U(IV) and U(VI). Tentative evidence in support of this mechanism has been provided by Renshaw et al (2005) and Grossmann et al (2007), but further work is required to unambiguously demonstrate the relevance of this reduction pathway.…”
Section: Biological Reduction and Uraninite Precipitationmentioning
confidence: 98%
“…Natural attenuation processes such as bacterial reductive/precipitation and immobilization of soluble uranium is gaining much interest (Dodge and Francis, 2008). For example, dissimilatory metal-reducing microorganisms have been investigated for their capability to selectively remove uranium from aqueous solutions (Lovley et al, 1992;Renshaw et al, 2005). These bacteria can use U(VI) as an electron acceptor thereby reducing soluble U(VI) to the precipitable tetravalent state [U(IV)] (Lovley et al, 1992;Lloyd and Renshaw, 2005;.…”
Section: Introductionmentioning
confidence: 99%